A43: Juvenile Idiopathic Arthritis in Relation to Maternal Prenatal Smoking. Issue 11 (March 2014) - Shenoi, Susan; Bell, Samantha; Wallace, Carol; Mueller, Beth
Abstract : Background/Purpose: Cigarette smoking increases the risk of seropositive adult Rheumatoid arthritis. Juveinile idiopathic arthritis (JIA) is a heterogenous group of 7 mutually exclusive categories of chronic childhood inflammatory arthritides. Objectives: To determine the association between JIA and its categories with maternal prenatal smoking. Methods: This case‐control study used ICD‐9 codes from hospital records to identify 1196 JIA cases born in Washington State and diagnosed at a tertiary pediatric center during 1997—2010. Controls (n = 5618) were randomly selected from birth records of children without JIA, frequency matched on birth year. Prenatal smoking exposure was assessed from subjects' birth certificates. Chart review categorized JIA into ILAR categories. Odds ratios (OR) and 95% confidence intervals (CI) were calculated using logistic regression adjusted for maternal age and marital status. Results: We did not observe an increased risk of JIA in relation to maternal prenatal smoking. Prenatal smoking was reported less often among mothers of JIA cases (11%), than among control mothers (17%, OR 0.71, 95% CI: 0.58—0.87), a relationship somewhat more marked for oligoarticular/ extended oligoarticular JIA. Although the inverse relationship persisted after adjustment for maternal education or health insurance status, we cannot rule out the possibility that this effect may have been at least partially due to residual confounding by socio‐economic status. Conclusion: We did not observe an increased risk of JIA with maternal prenatal smoking.